Labyrinth of lies [large type] - Hannon, Irene (Hannon, Irene. Triple threat, 2021)
"When the daughter of a high-profile businessman disappears from an exclusive girls' boarding school, police detective Cate Reilly is tapped for an undercover assignment. It doesn't take her long to realize that beneath the veneer of polish and wealth, things are not as they seem at Ivy Hill Academy. But the biggest surprise of all? The only man she ever loved is also working at the school. Zeke Sloan has never forgotten Cate, but now isn't the best time for their paths to cross again. When their two seemingly disparate agendas begin to intertwine- and startling connections emerge among the players- the danger escalates significantly. But who is the mastermind behind the elaborate ruse? And how far will they go to protect their house of cards?"--